Circulating biomedical images: Bodies and chromosomes in the post-eugenic era. (December 2017) - Santesmases, María Jesús
This essay presents the early days of human cytogenetics, from the late 1950s until the mid 1970s, as a historical series of images. I propose a chronology moving from photographs of bodies to chromosome sets, to be joined by ultrasound images, which provided a return to bodies, by then focused on the unborn. Images carried ontological significance and, as I will argue, are principal characters in the history of human cytogenetics. Inspired by the historiography of heredity and genetics, studies on visual cultures, the conceptualization of circulation, and the sociology of pregnancy, I suggest that cytogenetics, through its focus on pregnancy, pregnant women, and their offspring, found strategic living materials that stabilized human chromosome studies as a biomedical, post-eugenics practice. The historicity of each path displays a wide circulation of objects, tools, and methods that condensed on images that shared in the centuries-old visual expertise that medicine and botany had manufactured.